Design of a Digital Marketing Strategy to Improve SMEs Sales Performance Using the Marketing Mix and PDCA Cycle: A Case Study of Ayam Geprek Selaras - Teofilus Bima Tara Adi Widodo; Heri Setiawan (Ann Publisher, 2026)
Background, Small and medium enterprises (SMEs) in the culinary sector often experience unstable sales performance due to limited marketing reach and intense market competition. Ayam Geprek Selaras SME continued to rely on conventional marketing strategies, resulting in fluctuating revenue and limited business growth potential. Aim: This study aims to design and implement a structured digital marketing strategy to improve SME sales performance by integrating the Marketing Mix (4P) framework with the PDCA (Plan-Do-Check-Act) cycle as a continuous improvement approach. Methods: This research employed a descriptive, qualitative case-study approach. Data were collected through field observation, structured interviews with the business owner, and analysis of operational and sales records. The proposed strategy includes optimizing Google Maps visibility, activating social media marketing, implementing emotional pricing and product bundling strategies, improving environmentally friendly packaging, and integrating online food delivery platforms such as GoFood, GrabFood, and ShopeeFood. Results: The implementation of the digital marketing strategy significantly improved business performance. The average monthly revenue increased from IDR 25,225,000 to IDR 35,255,000, representing a growth rate of 39.76% with. The value increased to approximately 1.72 times the initial value Conclusions: The integration of the Marketing Mix framework with the PDCA cycle proved effective in improving SME sales performance through a systematic digital marketing strategy Implication. This study provides a practical framework for SMEs to adopt structured digital marketing strategies and continuous improvement approaches to enhance competitiveness and achieve sustainable business growth in the digital economy.